Anak Jalanan di Simpang Lampu Merah Telanaipura Kota Jambi (Analisis Terhadap Dampak Eksploitasi Anak) - Yenti, Zarfina; Huda, Samsul; Piadi, Agus (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
The children on public road represent one of the social problem faced by indonesian nation. In every country in this world also find the same social problem as the problem of prostitution which is difficult to find the exact formula to handle it, as complicated as the problem of children on public road. The amount of waif is clearly increasing although it almost impossible to get the opening statistic. Government is assessed cannot do many things to save them. Everyday, the children on the public road are fear of various threat includes the bad behaviour of government officers. In Jambi, the problem of children on public road is complicated enough to solve because its handling is not just to give symphatic paid, so that the government should have the exact policy to handle it. Their social balance are need to think of because what they will be f they have imbalance social problem? this will result bad effect for their behaviour and environtment in the future.